So what am I actually taking this medicine for?. Issue 5 (18th May 2022) - Thompson, Angus
Abstract : Addressing gaps in patient knowledge on the purpose of their medicines requires a multifaceted approach, tailored to the needs of the individual. One strategy that may help is indication‐enriched prescribing and dispensing, suggests Angus Thompson.